Managing the Implementation Process of Educational System Reform in Israel. (2018) - Isbanionly, Manal; Danaiata, Doina; Hurbean, Luminita
Abstract: The reform based on meaningful learning is a change process which entered in the education system in Israel. Like complex change processes in large systems and organizations, organizational change success depends on internal and external processes and factors. The connection between external stakeholders and internal stakeholders is two-way and is even more emphasized when one talks about change (Mintzberg & Westly, 1992), as on one hand, external stakeholders can initiate by themselves an organizational change where success will depend on cooperation and application of the change by internal stakeholders (Ford et al., 2008). The performed research checked the correlation between the support of external stakeholders and internal stakeholders in the reform of meaningful learning and their link to its success. The research findings show that external stakeholders as inspectors and parents have a significant role in successful implementation of a reform and their link to the internal stakeholders - principals and teachers - is an important indicator to the implementation of the reform, moderate resistance, and the overall reform's success.